1999
DOI: 10.1159/000007236
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Action of Natural Carrageenans on Herpes simplex Virus Infection of Mouse Astrocytes

Abstract: The effects of the carrageenans 1T1 (λ-type), 1C1 (κ/ι-type) and 1C3 (ιι/ν-type), isolated from the red seaweed Gigartina skottsbergii, on herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2) infection of murine astrocytes were investigated. The three compounds were effective inhibitors of virus replication, as determined by a virus yield inhibition assay, in astrocytes as well as in Vero cells. The 50% inhibitory concentration was in the range of 0.9–3.6 and 0.4–3.2 μg/ml for astrocytes and Vero cells, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 11 publications
0
63
0
1
Order By: Relevance
“…Carrageenan is a selective inhibitor of several enveloped viruses, including such human pathogens as human immunodeficiency virus, herpes simplex virus (HSV), human cytomegalovirus, human rhinoviruses and others (Girond et al 1991;Marchetti et al 1995;Carlucci et al 1999;Caceres et al 2000;Zacharopoulos and Phillips 1997;Stiles et al 2008). Carrageenan acts primarily by preventing the binding or the entry of virions into cells (Buck et al 2006, Grassauer et al 2008).…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Carrageenan is a selective inhibitor of several enveloped viruses, including such human pathogens as human immunodeficiency virus, herpes simplex virus (HSV), human cytomegalovirus, human rhinoviruses and others (Girond et al 1991;Marchetti et al 1995;Carlucci et al 1999;Caceres et al 2000;Zacharopoulos and Phillips 1997;Stiles et al 2008). Carrageenan acts primarily by preventing the binding or the entry of virions into cells (Buck et al 2006, Grassauer et al 2008).…”
Section: Antiviral Activitymentioning
confidence: 99%
“…All measurements were carried out using six separate wells for each treatment. The concentration of the agent that reduced cell viability to 50% (CC 50 ) was calculated [21,22] .…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Several sulfated polysaccharides have been shown to possess anti-HSV activity, and many carrageenans (found mostly in red seaweed) have been shown to be active against HSV infections. Several in vitro studies have demonstrated IC 50 values of 0.4-5.6 μg/ml for different types of carrageenans (46)(47)(48), and several in vivo mouse models have also confirmed their effectiveness. In models of intravaginal HSV-2 infection, mice exhibited signs of significant protection (30,48), and were also protected from intraperitoneal infection when carrageenan was administered immediately after infection.…”
Section: Natural Products With Anti-herpes Simplex Virus Activitymentioning
confidence: 86%